Near-Death Experiences are Caused by the Separation of Consciousness from the Body: An NDE Scale Analysis - Mays, Robert; Mays, Suzanne (Journal of Scientific Exploration, 2024)
Near-death experiences (NDEs) cannot be defined merely as a collection of phenomenal features. An accurate definition needs to describe what NDEs essentially are, that is, what lies behind the phenomenal features. The definition would describe what happens in the experience to account for the different features; this can only be fully described in the context of an underlying theoretical framework. In this paper, we propose the mind entity framework, which holds that a human being is a nonmaterial mind united with the physical body. In an NDE, the mind, or seat of consciousness, separates from the body and operates independently of it until the mind returns to and reunites with the body. From this framework, we identified the nine NDE features from the 16 features of the NDE Scale (Greyson, 1983) that specifically imply the separation of the mind from the body. The five most prevalent of these “separation” features accounted for 98.8% of NDEs in a sample of NDE accounts in the IANDS Experience Registry (N=565). The prevalence of these five “essential” NDE features was repeated in three other large NDE datasets published in the last 20 years. Therefore, an NDE can be defined as a profound subjective experience caused by a person’s consciousness separating from their physical body.